Painful Bladder Filling and Painful Urgency Are Distinct Characteristics in Men and Women with Urologic Chronic Pelvic Pain Syndromes – A MAPP Research Network Study - Lai, H. Henry (J Urol, 2015)
PURPOSE: To describe bladder-associated symptoms in patients with urologic chronic pelvic pain syndromes (UCPPS) and to correlate these symptoms with urologic, non-urologic, psychosocial, and quality of life measures. METHODS: Participants were 233 women and 191 men with interstitial cystitis/bladder pain syndrome or chronic prostatitis/chronic pelvic pain syndrome in a multi-center study. They completed a battery of measures, including items asking if their pain worsened with bladder filling (“painful filling”) or if their urge to urinate was due to pain, pressure, or discomfort (“painful urgency”). Participants were categorized into 3 groups: 1) “both” painful filling and painful urgency, 2) “either” painful filling or painful urgency, or 3) “neither.” RESULTS: Seventy-five percent of men and 88% of women were categorized as “both” or “either.” These bladder characteristics were associated with more severe urologic symptoms (increased pain, frequency, urgency), higher somatic symptom burden, depression, and worse quality of life (all p<0.01, 3-group trend test). A gradient effect was observed across groups (both > either > neither). Compared to those in the “neither” group, men categorized as “both” or “either” reported more frequent UCPPS symptom flares, catastrophizing, and irritable bowel syndrome, and women categorized as “both” or “either” were more likely to have negative affect and chronic fatigue syndrome. CONCLUSIONS: Men and women with bladder symptoms characterized as painful filling or painful urgency had more severe urologic symptoms, more generalized symptoms, and worse quality of life than participants who reported neither characteristic, suggesting that these symptom characteristics might represent important subsets of UCPPS patients.